"Zipper" Concept for Designing Expanded Forehead Flap in Facial-Cervical Reconstruction. Issue 4 (June 2021) - Chen, Hongbo; Su, Zhiguo; Tian, Jia
Abstract : Background: Skin defect of the lower part of the face and neck is a severe condition for many patients with burn and traumatic injuries or skin lesions. The expanded forehead flap with anterofrontal temporal vessel pedicles has been widely used in lower cheeks, chin, and neck reconstruction. (In this study, we introduce a new concept- "Zipper concept" of the flap design.) The aim of this study is to evaluate the feasibility and outcome of using expanded forehead flap with a vertical incision with or without a small transverse incision in the central part. Methods: From March 2010 to September 2016, 27 patients who suffered from lower cheeks and chin skin defects were reconstructed by expanded forehead flap with anterofrontal temporal vessel pedicles. After the lesion was excised, the upper or the lower part of the flap was cut in half with a vertical incision with or without a small transverse incision in the middle part as needed for cheeks, upper lip or neck reconstruction, and the other part of the flap was remained to be one piece for chin reconstruction. Results: All flaps survived completely without any congestion or necrosis. All patients achieved satisfactory results both functionally and aesthetically. Conclusions: A vertical incision with or without a small transverse incision in the central part of the expanded forehead flap with anterofrontal temporal vessel pedicles is a safe modification of the flap design. It is practical and could bring the expanded forehead flap to more indications. Abstract : Supplemental Digital Content is available in the text